MODL-31. PHOTORECEPTOR-POSITIVE PROGENITORS PUTATIVE CELLS OF ORIGIN IN MYC-DRIVEN GROUP 3 MEDULLOBLASTOMA. (14th November 2022) - Zhao, Miao; Mainwaring, Oliver; Rosén, Gabriela; Olsen, Thale Kristin; Rijpkema, Sanne; Sundström, Anders; Weishaupt, Holger; Furukawa, Takahisa; Swartling, Fredrik
Abstract: The cell of origin of Group 3 medulloblastoma, the most malignant medulloblastoma subgroup, is currently unknown and remains controversial. Transcriptional profiling has revealed that Group 3 medulloblastomas are characterized by elevated expression of a photoreceptor program, which has not been described in the normal cerebellar development but is well characterized in the developing retina and pineal gland. We used lineage tracing and single-cell sequencing to compare normal brain development with tumor development in our previously generated MYC-driven transgenic mouse model (GMYC), where mice spontaneously develop Group 3 medulloblastoma after 4-6 months of age. We found that tumor cells emerged from progenitor cells where MYC overexpression drove the transformation of immature progenitor cells with photoreceptor pathway activity. Our data suggest that MYC-driven Group 3 medulloblastoma originates from progenitor cells expressing a photoreceptor program, which has implications for future research and the development of novel treatments targeting this devastating childhood malignancy.